Effectiveness of a multicentre randomized controlled trial with three different nurse-led intervention management programmes for patients with heart failure: the main results of the MEETinCY study - Lambrinou, Ekaterini; Protopapas, Andreas; Paikousis, Lefkios; Middleton, Nicos; Papathanassoglou, Elizabeth; Sourtzi, Panayota; Kaloyirou, Fotini (My University, 2025)
A single-blinded, multicentred randomized controlled trial (RCT) was employed to examine the effectiveness of a 3-month telephone follow-up, a telephone follow-up with education before discharge, or education only before discharge on the heart failure (HF) knowledge, HF self-care management, and health-related quality of life (HR-QoL) in patients with HF by a nurse specialist.
Keywords: Education and telephone follow-up interventions; Heart failure; Nurse-led interventional management programmes; Randomized controlled trial (RCT); Telemonitoring